Incident Response with Threat Intelligence : Practical Insights into Developing an Incident Response Capability Through Intelligence-Based Threat Hunting - Martinez, Roberto (Packt Publishing, 2022)
Learn everything you need to know to respond to advanced cybersecurity incidents through threat hunting using threat intelligence Key Features Understand best practices for detecting, containing, and recovering from modern cyber threats Get practical experience embracing incident response using intelligence-based threat hunting techniques Implement and orchestrate different incident response, monitoring, intelligence, and investigation platforms Book Description With constantly evolving cyber threats, developing a cybersecurity incident response capability to identify and contain threats is indispensable for any organization regardless of its size. This book covers theoretical concepts and a variety of real-life scenarios that will help you to apply these concepts within your organization. Starting with the basics of incident response, the book introduces you to professional practices and advanced concepts for integrating threat hunting and threat intelligence procedures in the identification, contention, and eradication stages of the incident response cycle. As you progress through the chapters, you'll cover the different aspects of developing an incident response program. You'll learn the implementation and use of platforms such as TheHive and ELK and tools for evidence collection such as Velociraptor and KAPE before getting to grips with the integration of frameworks such as Cyber Kill Chain and MITRE ATT & CK for analysis and investigation. You'll also explore methodologies and tools for cyber threat hunting with Sigma and YARA rules. By the end of this book, you'll have learned everything you need to respond to cybersecurity incidents using threat intelligence. What you will learn Explore the fundamentals of incident response and incident management Find out how to develop incident response capabilities Understand the development of incident response plans and playbooks Align incident response procedures with business continuity Identify incident response requirements and orchestrate people, processes, and technologies Discover methodologies and tools to integrate cyber threat intelligence and threat hunting into incident response Who this book is for If you are an information security professional or anyone who wants to learn the principles of incident management, first response, threat hunting, and threat intelligence using a variety of platforms and tools, this book is for you. Although not necessary, basic knowledge of Linux, Windows internals, and network protocols will be helpful.
Discovering and containing malicious behaviors.
Keywords: Cyber intelligence (Computer security); Computer crimes -- Investigation.; elektronické knihy; electronic books